SELECTIVE COLLECTION AND RECYCLING OF SOLID WASTE CASE STUDY: RECYCLING OF SOLID WASTE IN HULENE KA-MAHOTA DISTRICT - ElijaGuamba, Jose Manuel; AmericoTembe, Arnaldo (International Journal of Research -GRANTHAALAYAH, 2016)
The waste collected daily from household and businesses entities can be utilized for various objectives, serving as raw material for business and other most appropriate purposes. You can, for example, recycle plastic, produce compost and energy, recovering the economic value of such waste. Waste recycling generates jobs and income, reduces the amount of natural resources needed for a new product and also decreases the need to occupy (and pollute) space to deposit materials that have served only once their socio-economic function. And what you can't recycle always has another proper disposal, as a principle which is basic in the concept of sustainable development: Do not transfer the solution of the problem for future generations. The aim of this study is to evaluate the panorama of the selective collection of household waste from the case study of plastic recycling in the neighborhood of Hulene Dump side, at municipality of Maputo. The methodology used in this research was the bibliographical and documentary analysis, as well as semi-structured qualitative interviews with: representative of Municipal Department of Waste Management, Health and Water Supply in the Maputo municipality; administrative coordinators of four organizations studied (RECICLA and FERTILIZA cooperatives, AMOR and PAGALATA associations). Additionally, technical visits were carried out with written and photographic records, interviews to members of the RECICLA cooperative.